규제개혁 이슈의 생존 주기와 규제개혁 동력에 관한 연구: 이명박과 박근혜 정부의 비교 - 박기묵; Kimuck Park (국가정책연구, 2021)
이 연구는 이명박과 박근혜 정부의 규제개혁 이슈의 이슈 생존 주기를 조사함으로써 두 정부의 규제개혁 이슈의 이슈 생존 주기에서 나타나는 그 유형의 차이와 대중의 관심이 집중되는 시기의 뉴스 내용분석을 통해 두 정부의 규제개혁 정책의 차이점을 찾아내고, 그 차이가 보여주는 정책적 함의를 제시하였다. 연구의 결과, 이명박 정부는 외부로부터 규제개혁 환경이 조성됐지만, 박근혜 정부는 정부 내부에서 인위적으로 규제개혁 환경을 조성한 것으로 나타났다. 이명박 정부의 규제개혁은 크게 성공을 거둘 수 있는 외적 환경 및 다른 조건들을 가졌던 반면, 박근혜 정부는 그렇지 못했다는 것을 발견하였다. 이 연구는 이를 통해 규제개혁의 성공적 추진을 위한 핵심 조건들을 찾을 수 있었다. 그것들은 세 가지로 요약될 수 있는데, 첫째는 규제개혁 이슈의 사회적 이슈화, 둘째는 대통령 임기 초 규제개혁정책 착수, 셋째는 대통령의 규제개혁 추진 의지였다. 이 연구에서는 또한 정성적 연구에서 필요한 코더 간 신뢰성(Inter-coder Reliability)과 관련된 논의를 소개하였고, 실제로 신뢰성을 보여주는 Krippendorff α값을 제시함으로써 정성적 연구의 신뢰성을 보여주었다. 0This study examines the life cycle of the regulatory reform issues of the Lee Myung-bak and Park Geun-hye governments, and investigates the differences in the types of regulatory reform issues in the life cycle of the two governments and the regulation of the two governments through the analysis of news content at a time when public attention is focused. The differences in reform policies were identified, and the policy implications of the differences were presented. As a result of the study, it was found that the Lee Myung-bak administration created an environment for regulatory reform from the outside, but the Park Geun-hye administration created an environment for regulatory reform artificially within the government. It was found that while the Lee Myung-bak administration's regulatory reform had external circumstances and other conditions to be highly successful, the Park Geun-hye administration did not. Through this study, it was possible to find the key conditions for the successful implementation of regulatory reform. They can be summarized into three categories. First, the regulatory reform issue became a social issue, the second was the initiation of the regulatory reform policy at the beginning of the president's tenure, and the third was the president's will to promote regulatory reform. This study also introduced the discussion related to inter-coder reliability required for qualitative research, and showed the reliability of qualitative research by presenting the Krippendorff value that actually shows reliability.